Construction of a police physical evaluation model and standards based on law enforcement ability - Feng, Yuliang; Liu, Yang; Wang, Dexin (Frontiers in Physiology, 2024)
Purpose: In the context of police practical combat with the essence of coercion and confrontation, police physical fitness training guided by practical combat is increasingly valued. The objective of this study was to establish a police physical evaluation model and standard based on law enforcement ability. Methods: Using literature analysis, expert interviews, Delphi method, field testing, and mathematical statistics, the test results of 301 frontline law enforcement police officers from the Shanghai Public Security Bureau were used as sample data. Factor analysis was conducted on the selected indicators to determine the final indicator system for police physical fitness. The percentile method was used to develop evaluation standards, and frequency statistics and chi square tests were used to calculate the effectiveness and accuracy of the evaluation standards.: Research has found that the police physical fitness evaluation model based on law enforcement ability is: Y=0.115 × Pull the trigger in 30 seconds+0.105 × 30 second straight punching sandbag+0.095 × 30 second drop dummy+0.062 × Push ups+0.115 × 50 meter run+0.095 × 10 meters × 4 round trips+0.116 × Standing Long Jump+0.090 × 2000 meter run+0.089 × 30 second short baton chopping sandbags+0.118 × 30 second long baton poking sandbags; The evaluation criteria are divided into single item and comprehensive evaluation criteria. Conclusion: A practical police physical fitness evaluation model can effectively evaluate the level of police physical fitness development, and evaluation standards can provide effective basis for practical police physical fitness evaluation.